Decreased Apoptotic Rate of Alveolar Macrophages of Patients with Idiopathic Pulmonary Fibrosis - Fotios Drakopanagiotakis; Areti Xifteri; Evaggelos Tsiambas; Andreas Karameris; Konstantina Tsakanika; Napoleon Karagiannidis; Demetrios Mermigkis; Vlasis Polychronopoulos; Demosthenes Bouros (Pulmonary Medicine)
Introduction. Increased apoptosis of epithelial cells and decreased apoptosis of myofibroblasts are involved in the pathogenesis of IPF. The apoptotic profile of alveolar macrophages (AMs) in IPF is unclear. Aim. To investigate whether AMs of patients with IPF exhibit a different apoptotic profile compared to normal subjects. Methods. We analyzed, by immunohistochemistry, the expression of the apoptotic markers fas, fas ligand , bcl-2, and bax in AM obtained from bronchoalveolar lavage fluid (BALF) of 20 newly diagnosed, treatment-naive IPF patients and of 16 controls. Apoptosis of AM was evaluated by Apoptag immunohistochemistry. IPF patients received either interferon-g and corticosteroids or azathioprine and corticosteroids for six months. Results. BALF AMs undergoing apoptosis were significantly less in IPF patients. No difference was found in the expression of fas or fas ligand, bcl-2 and bax between IPF and control group. No difference was found between the respiratory function parameters of the two treatment groups after six months. A positive correlation was found between the number of bcl-2 positive stained macrophages and DLCO after treatment. Conclusions. The decreased apoptotic rate of AM of patients with IPF is not associated with decreased expression of apoptosis mediators involved in the external or internal apoptotic pathway.